Beleuchtungsverfahren zur problemspezifischen Bildgewinnung für die automatische Sichtprüfung (2013)
In machine vision, the illumination design has direct impact on the performance of a visual inspection system. In this work, a problem-specific illumination design is presented, which is motivated by optical feature extraction taking place during physical image acquisition. The approach is analyzed on the basis of a physically based camera and illumination model and is experimentally evaluated in different application scenarios.